Expectativas, percepções e opiniões de mulheres sobre o atendimento durante o parto - COSTA, Nara dos Santos (2016)
It is accepted that, in most part of care environments, women under labor or delivery are submitted to care service according to what the health establishment wants and not the way they expect to be treated. It would be essential that the health care could meet the women’s expectancies and their real necessities, being able this way to offer humanized care together with the professionals, the usage of technology, quality tools and proper facilities. In the face of these facts, from the women’s reported speech, the need of searching for the right of access to quality health service is born, in which the respect for the many dimensions, individuality, perspective and impressions occupy primordial spaces. This research had the general goal of describing the satisfaction of women that had the delivery experience in terms of received service. It is a qualitative, descriptive research, with a cuali-quantitative approach. The research was taken in two hospitals linked to the health public system in the city of Uberaba, Minas Gerais, Brazil, with the participation of 104 women. The data was collected in the period between July and October 2015, thorough interviews during the prenatal and postpartum periods, an interview script, composed of two moments, was applied. At the first moment, a comic strip about pregnancy, aiming to know the pregnant women’s expectations was presented, at a second moment, there were questions about the characterization of the interviewed women, questions related to the perception about service and possible actions to be implemented with the aiming of the improving of labor assistance. The information about the interviewed characterization was submitted to descriptive analyses, with the calculation of absolute and percentage frequencies. The results related to the interview transcription were exposed to the Collective Subject Speech analyses method, which consists of tabulation and organization of qualitative data, with the assistance of software QualiQuantsoft®. The results showed that 68 women were from hospital A and 36 from hospital B, with an age average of 27 years old. With the results found, it is possible to consider that women’s satisfaction in relation to labor service is given by the attitude aspects and professional conduct, as well as, the presence of an accompanying person and the institution’s facilities. With 102 key-expressions, the questions related to the professional attitude and practice were the most expressive ones, followed by the focus on the accompanying person with 18 key-expressions. As labor assistance improvement proposal, the interviewed women raised the following topics: proposals to the health staff and proposals of infrastructure and equipment. The results allow us to conclude that pregnant women and women who have recently given birth are satisfied with the received service during labor, mainly the matters related to the interaction between the staff. The patients showing that these aspects contribute to the improvement of health service and show that the satisfaction is strictly connected with the quality of the received health assistance.